FORMULATION AND CHARACTERIZATION OF MUCOADHESIVE MATRIX TABLET OF NIZATIDINE - Gupta, Saritadevi; Dev, Asish (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the work is to formulate nizatidine mucoadhesive matrix tablets which will significantly improve the bioavailability of drugs under the condition of prolonged use of drugs and reduce the total dosage of administered drug and reduce the side effect. Method: Matrix tablet was prepared by direct compression of polymer such as HPMC K4M, carbopol-934p, and ethyl cellulose alone and in combination. Result: After analysis of different evaluation parameter and drug release, F9 batch was selected as promising formulation for delivery of nizatidine as a mucoadhesive matrix tablet with 94.18% drug release at the 12th h. Conclusion: It was observed that the combination of both polymers in equal concentration gives the best drug release and sustains the drug release for 12 h. Among the other batches, F9 batch was selected as an optimized batch because the pre- and post-compression parameter results are satisfactory.